Antifungal and Antioxidant Activities of Lipophilic Compounds from Swietenia mahagoni (l.) Jacq. Leaves - Masendra Masendra; Brandon Aristo Verick Purba; Rizki Arisandi; Ganis Lukmandaru (Wood Research Journal, 2015)
The investigation on the n-hexane lipophilic extractives of Swietenia mahagoni, alongside the antifungal and antioxidant properties was conducted. The leaf sample was collected from 2- and 3-years-old trees in Perhutani enterprise of Temanggung, Central Java, Indonesia. In addition, the antifungal activity was tested using the white-rot of Phanerochaete chrysosporium, while the antioxidant property involved the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The results show antifungal of 28.6% and 37.5% growth inhibition in 2- and 3 -years-old leaf, respectively, while 21.7% and 25.4% antioxidant activity were also recorded. Furthermore, the GC-MS results showed the domination of S. mahagoni leaf by fatty acids and hydo-carbons, while the terpenoids and steroids were in minor quantities. These components possibly exhibit growth inhibitory and antioxidant effects against P. chrysosporium and DPPH radicals, respectively.